Comparative Proteomic Analysis of Psychrophilic vs. Mesophilic Bacterial Species Reveals Different Strategies to Achieve Temperature Adaptation - García-Descalzo, Laura; García-López, Eva; Cid, Cristina (Frontiers in Microbiology, 2022)
The old debate of nature (genes) versus nurture (environmental variables) is once again topical concerning the effect of climate change on environmental microorganisms. Specifically, the Polar Regions are experiencing a drastic increase in temperature caused by the rise in greenhouse gas emissions. This study, in an attempt to mimic the molecular adaptation of polar microorganisms, combines proteomic approaches with a classical microbiological analysis in three bacterial species Shewanella oneidensis, Shewanella frigidimarina, and Psychrobacter frigidicola. Both Shewanellas are members of the same genus but they live in different environments. On the other hand, Shewanella frigidimarina and Psychrobacter frigidicola share the same natural environment, but belong to a different genus. The comparison of the strategies employed by each bacterial species estimates the contribution of genome versus environmental variables in the adaptation to temperature. The results show a greater versatility of acclimatization for the genus Shewanella with respect to Psychrobacter. Besides, S. frigidimarina was the best-adapted species to thermal variations in the temperature range 4ºC-30ºC and displayed several adaptation mechanisms common with the other two species. Regarding the molecular machinery used by these bacteria to face the consequences of temperature changes, chaperones have a pivoting role. They form complexes with other proteins in the response to the environment, establishing cooperation with transmembrane proteins, elongation factors, and proteins for protection against oxidative damage.